Accelerated Early Vascular Aging Among Adolescents With Obesity and/or Type 2 Diabetes Mellitus. Issue 10 (18th May 2020) - Ryder, Justin R.; Northrop, Elise; Rudser, Kyle D.; Kelly, Aaron S.; Gao, Zhiqian; Khoury, Philip R.; Kimball, Thomas R.; Dolan, Lawrence M.; Urbina, Elaine M.
Abstract : Background: The normal rate of subclinical vascular aging from adolescence to young adulthood has not been well‐characterized. We conducted a 5‐year longitudinal study among adolescents with normal‐weight, obesity, and/or type 2 diabetes mellitus to examine trajectories of early vascular aging. Methods and Results: Adolescents (mean [SD] age 17.6 [3.5]; 35.3% male) had either normal weight (n=141), obesity (n=156), or type 2 diabetes mellitus (n=151) at baseline. Primary metrics used for early vascular aging included measures of vascular structure (carotid intima‐media thickness [cIMT]; common, internal, and bulb) and arterial stiffness (carotid‐femoral pulse wave velocity, and augmentation index). Longitudinal (5‐year) outcomes were examined using generalized estimating equations adjusting for baseline value, sex, race, and age. Compared with participants with normal weight, those with obesity had greater positive change in common cIMT (0.05 mm [0.03, 0.06]; P <0.001), bulb cIMT (0.02 mm [0.00, 0.05]; P =0.033), internal cIMT (0.03 mm [0.01, 0.05]; P <0.001), and pulse wave velocity carotid‐femoral (0.38 m/sec [0.14, 0.61]; P =0.001), and those with type 2 diabetes mellitus had greater positive change in common cIMT (0.05 mm [0.04, 0.07]; P <0.001), bulb cIMT (0.06 mm [0.04, 0.09]; P <0.001), internal cIMT (0.04 mm [0.02, 0.07]; P <0.001), augmentation index (4.67% [2.20, 7.13]; P <0.001), and pulse wave velocity carotid‐femoral (0.74 m/sec [0.46, 1.02]; P <0.001). Higher baseline systolic blood pressure was associated with greater positive change in common cIMT (0.007 mm [0.003, 0.011]; P <0.001), bulb cIMT (0.009 mm [0.002, 0.016]; P =0.01), internal cIMT (0.008 mm [0.003, 0.013]; P =0.001), and pulse wave velocity carotid‐femoral (0.066 m/sec [0.002, 0.130]; P =0.042). Conclusions: These longitudinal data support the hypothesis that the presence of obesity, type 2 diabetes mellitus, and elevated baseline systolic blood pressure in early life accelerates the progression of risk factors key in the development of early vascular aging.